2014
DOI: 10.1016/j.mgene.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of the rs11196218 polymorphism in TCF7L2 with type 2 diabetes mellitus in Asian population

Abstract: ObjectiveTo clarify the association of rs11196218 polymorphism in transcription factor 7-like 2 (TCF7L2) and type 2 diabetes mellitus (T2DM) in Asian population by a case–control study and meta-analysis.MethodsIn the case–control study, 1842 patients with T2DM and 7777 normal glucose-tolerant controls in the Henan province of China were genotyped for rs11196218 in TCF7L2 by PCR–ligase detection reaction. We used allele, co-dominant, dominant and recessive models to evaluate the risk association and performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Qian et al (2015) conducted a quantitative trait analysis and showed that the AC genotype of rs1552224 presented higher FBG than the AA/CC genotypes in a control population with normal glucose. Mechanistic studies suggest that TCF7L2 can impair β-cell function, and down regulate the expression levels of glucagon-like peptide 1 receptor (GLP-1R) and glucose-dependent insulinotropic polypeptide receptor (GIP-R), thereby reducing insulin levels (Zhai et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Qian et al (2015) conducted a quantitative trait analysis and showed that the AC genotype of rs1552224 presented higher FBG than the AA/CC genotypes in a control population with normal glucose. Mechanistic studies suggest that TCF7L2 can impair β-cell function, and down regulate the expression levels of glucagon-like peptide 1 receptor (GLP-1R) and glucose-dependent insulinotropic polypeptide receptor (GIP-R), thereby reducing insulin levels (Zhai et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 295 articles were relevant to our search terms, of which 285 papers were excluded. Thus, 10 case-control studies 15 – 19 , 30 – 34 comprising 7,491 cases of T2DM and 12,968 controls were ultimately included in this meta-analysis ( Figure 1 ). All of these studies were published from 2007-2014.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the results regarding the rs11196218A/G polymorphism and T2DM risk have been inconsistent for the Chinese Han population. Certain studies 15 – 19 confirmed that the G allele of the rs11196218A/G polymorphism was significantly associated with T2DM risk, whereas studies by Ma 30 , Zheng et al 31 , Luo et al 32 , Wen et al 33 and Qiao et al 34 did not find a significant association between the rs11196218A/G polymorphism and T2DM risk in the Chinese Han population. Therefore, to resolve the conflict among these studies, we performed a meta-analysis to assess the association between the rs11196218A/G polymorphism and T2DM risk.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…T2DM is a complex disease and both genetic, and environmental factors appear to contribute to its development. [ 8 9 10 ]…”
Section: Introductionmentioning
confidence: 99%